The Cosmological Gnosis of Miguel Serrano - Versluis, Arthur (Gnosis, 2022)
A close look at a very unusual instance of how gnosis, and specific concepts from early Christian-era Gnosticism, appear directly in the numerous late works of a recent Chilean author, Miguel Serrano (1917–2009), and of how his work and thought exemplifies cosmological gnosis. Many international readers knew Serrano as author of unusual fictional works, and as an ambassador for Chile to several countries. During his time abroad, he met, and in many cases befriended, famous figures of the day, including Carl Jung, Herman Hesse, Ezra Pound and the fourteenth Dalai Lama. But fewer are aware of his works promoting a grand cosmological synthesis of many world religious traditions with esoteric Hitlerism expressed in gnostic terms. His syncretic system includes references to a demiurge and to gnosis, as well as to many other esoteric traditions from Europe, India, Tibet, and elsewhere, largely in a Gnostic context. This article by Arthur Versluis is the first to explore this aspect of Serrano’s work.